2021
DOI: 10.3390/microorganisms9112402
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota Parameters Potentially Useful in Clinical Perspective

Abstract: Interest in gut microbiota analyses is at an all-time high. Gut microbiota is thought to relate to an increasing range of diseases of interest to physicians and nutritionists. Overweight, obesity, response to diet, metabolic syndrome, low grade inflammation, diabetes and colon neoplasms could maybe be observed in microbiota if affordable markers were available. Possible biomarkers like the Firmicutes/Bacteroidetes ratio, the Gram-positive/Gram-negative ratio, the Prevotella/Bacteroides ratio, and the Fusobacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 98 publications
2
24
0
4
Order By: Relevance
“…Consistent with our results, other studies have reported that Fusobacteria are associated with host lipid metabolism [ 61 ]. Bacteroidetes also are Gram-negative anaerobic bacteria [ 62 ] that are closely associated with the occurrence and development of intestinal inflammatory diseases [ 63 ]. In this study, transport stress resulted in a reduced abundance of Bacteroidetes and an increase in the Firmicutes/Bacteroidetes ratio in hybrid yellow catfish.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our results, other studies have reported that Fusobacteria are associated with host lipid metabolism [ 61 ]. Bacteroidetes also are Gram-negative anaerobic bacteria [ 62 ] that are closely associated with the occurrence and development of intestinal inflammatory diseases [ 63 ]. In this study, transport stress resulted in a reduced abundance of Bacteroidetes and an increase in the Firmicutes/Bacteroidetes ratio in hybrid yellow catfish.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that DEX increased the relative quantity of Firmicutes and the Firmicutes to Bacteroidetes ratio, further reversing the intestinal I/R-induced microbiota abnormalities. Firmicutes and Bacteroidetes are 2 major phyla in normal intestinal microbiota, and the Firmicutes to Bacteroidetes ratio has been associated with several pathological conditions ( 36 ). Huang et al found that a high-fiber diet increased the quantity of Firmicutes and reduced the incidence of rectal cancer ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Smoking tobacco is reported as the gut microbiome alteration promotor. In the human study, the model exhibited the elevation of most gram-negative microbes: Firmicutes and Proteobacteria, whereas decreasing anaerobe microbe Bacteroidetes [43]- [46]. This alteration is associated with LPS high prevalence, increasing TLR-4 mRNA expression, signaling VN through α5 nAChR resulting in proinflammatory mediator secretion ISSN: 2252-8938 ïČ…”
Section: 𝑅 =mentioning
confidence: 95%